Mission Santa Inez - Kessler, Friedolin Edward:::Creator:::::::::::: (Kessler, Friedolin Edward)
Linoleum cut print of Mission Santa Inez on paper, pasted on front of greeting card. In cursive at bottom of card, Mission Santa Inez by Friedolin Kessler.